The Influence of Job Motivation, Perceived Organizational Support Indicators, and Demographic Characteristics on Job Satisfaction of Pharmaceutical Sales Executives in Nigeria - Oamen, Theophilus Ehidiamen (Journal of Pharmacy Practice and Community Medicine)
Objectives: More pharmacy practice research has to be done to investigate the impact of Perceived organizational support (POS), demographics, and Job motivation (JM) on Job satisfaction (JS) of pharmaceutical sales executives (PSE) in the pharmaceutical marketing industry. The objectives of the study were to evaluate the predictive effects of POS, JM, and demographic attributes of PSE on JS. Secondly, explore the relationship between POS indicators and demographic variables of respondents. Methods: A crosssectional online survey of 406 pharmaceutical sales executives, conducted between April to May 2021 in Nigeria using a random sampling method. Results: Correlations existed between Age vs. Training and Career prospects: Marital status vs. Incentive-scheme and Career prospects: Type of pharmaceutical company vs. Work-tools availability, Training, Incentive-scheme, marketing support, and career prospects: Years of experience vs. Training, Incentive, reward system, and career prospects: Annual salary vs. worktools, Incentives, and marketing support. The study model met acceptable fit criteria. Overall satisfaction score was 1.54±0.499, and motivation score was 1.37±0.484 respectively. The mean satisfaction rating score was ambivalent on the 5-point scale with 2.73 (SD=0.90), and the Motivation score was 2.49 (SD=0.95) indicative of low JM. Aggregate POS (1.88±0.734) and respondents’ perception of the pharmaceutical marketing industry was poor (2.10±0.83). The regression model showed that Marital status had a positive predictive relationship (β=0.606) compared to Motivation (β=- 2.614), Reward system (β=-0.866), and Work tools availability (β=-0.365), were predictors of JS at p<0.05. Conclusion: Study outcomes provided valuable human resource information to support policy reforms in the pharmaceutical marketing industry.
Keywords: Demographics; Job satisfaction; Job motivation; Perceived organizational support; Pharmaceutical sales executives; Pharmaceutical Marketing; Nigeria; Management